Study of wake meandering by means of fixed point lidar measurements: Spectral analysis of line-of-sight wind component. (June 2015) - Trabucchi, Davide; Steinfeld, Gerald; Bastine, David; Trujillo, Juan-José; Schneemann, Jörge; Kühn, Martin
Abstract: The validation of dynamic wake meandering models by full field measurements is an important but challenging task. Recently a new approach has been proposed, where a long range lidar was employed to analyse the power spectral density of the line of sight wind component measured across the wake trajectory. The method is promising, but the number of useful time series within a measurement campaign depends to a large extent on a favourable geometrical setup of the lidar position and the wind direction. In the first part of the paper the approach is further investigated. To this avail, lidar simulations based on large eddy simulation results are analysed. In the second part, the approach is applied to real measurement data from a campaign with a long range lidar windscanner in the offshore wind farm "alpha ventus". Eventually results about the wake dynamics are discussed.